Biological Interplay between Orthodontic Forces and Apical Papilla-derived Stem Cells: A Review on Mechanisms and Implications - Sobhani, Maryam; Bathaei , Yasaman; Afzalan, Alireza; Hormozi, Sepideh; Shanehsaz, Zeinab; Nabizadeh, Sara; Gashtasb, Kosar (Galen Medical Journal, 2025)
Background: Orthodontics is not limited to the movement of teeth, but has also expanded to the cellular and molecular realms. In this study, it was aimed to review mechanisms and implications of biological interplay between orthodontic forces and apical papilla-derived stem cells. Materials and Methods: This narrative and semi-systematic review investigates the biological interactions between orthodontic forces and stem cells derived from the apical papilla (SCAPs). A comprehensive literature search was conducted in PubMed, Web of Science, and Google Scholar using specific keywords and MeSH terms from 2015 to 2025. Studies in English and Persian were included if they focused on the effects of orthodontic forces on SCAPs’ function, differentiation, or signaling pathways. Key biological mechanisms and molecular responses were extracted and analyzed. Results: Between 2015 and 2025, 10 studies were included, primarily investigating human dental stem cells (SCAPs, DPCs, PDLSCs, SHEDs) and rat models. Findings showed that advanced glycation end-products inhibit osteogenesis via KDM6B and Wnt/β-catenin suppression, whereas Ape1 inhibition promotes odontogenic differentiation through the same pathway. Nano-dentine enhanced osteogenic gene expression compared to MTA and Biodentine, and low-energy blue LED stimulated osteogenic differentiation despite reduced proliferation. TGF-β1 had dose-dependent effects on SCAP proliferation and differentiation, while FTO/SMOC2 regulated odontoblastic differentiation under inflammatory conditions. Mechanical forces reduced SHED proliferation without affecting apoptosis, and pathogenic bacteria like F. nucleatum and E. faecalis impaired SCAP proliferation, viability, and osteogenic gene expression, indicating that molecular, material, mechanical, and microbial factors critically modulate dental stem cell differentiation. Conclusion: Current evidence shows that various physical, chemical, microbial, and molecular factors influence dental stem cell behavior. Understanding these mechanisms can support the development of personalized therapies, enhancing outcomes in endodontic and orthodontic treatments, particularly under pathological conditions like diabetes and chronic inflammation.